Personal Load Carrier Vehicle With Automatic Following Capability - Majid, Muhammad Fakhrurazi Majid; Talib, Rahmat (Evolution in Electrical and Electronic Engineering, 2022)
Every supermarket has shopping carts to help customers choose their desired products. There are a lot of bustles in the mall during festivals and special offers. In shopping malls or supermarkets, trolleys are frequently used. It will usually cause a collision with the trolleys or the shelves around it. Trolleys are also frequently changed by the users, which is very dangerous for the current situation plagued by this COVID-19 situation. This condition will cause the virus to spread if there is no immediate action taken. To avoid this issue, we propose a solution which is the design capable to replace the trolley. This invention is able to carry goods and follow the user automatically to overcome this problem. It is built with sensors that will help to detect its owner and move as directed. The presence of this product will also reduce the risk of COVID-19 virus transmission among consumers as they will no longer have to share their carts with other customers. Moreover, this new invention is not limited to shopping; it can also be used anywhere by consumers according to their wishes.